Peningkatan Hasil Belajar IPS dengan Model Pembelajaran Kooperatif Tipe Team Games Tournament Berbantuan Media Visual Pada Kelas VII-5 SMP Muhammadiyah Palangka Raya - Sapti Chusniati; Aidin Najihi (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2018)
This study aims to find out: How learning activities and improving student learning outcomes by using the Team Games Tournament Cooperative learning model (TGT) Assisted by Visual Media in class VII-5 of Palangka Raya Muhammadiyah Middle School. This research is classroom action research (CAR). The number of research subjects was 23 students. The results of this study are: There is an increase in student learning activities, namely the score of learning activities of students in the second cycle there are 21 students who get a score of 00 3.00 and 2 students who get a score of 00 3.00 with an average score of 33, 36, so that the learning activities of students in the second cycle have been said to be good or have achieved indicators of success. learning outcomes of Social Sciences (IPS) when Pre Test obtained an average value of 39.34 with completeness in classical 4.34%. In the post-test, the first cycle obtained an average value of 53.47% with completeness in classical 30.43%. And the post-test cycle II increased with an average value of 81.30 with completeness in classical 91.30%.